Efforts To Reduce Rm-1 Refiner Disturbances At Pt Pln (Persero) Ulp Rimo From The Chronic Category With Network Maintenance Based On Inspections Using Thermacam - Adolf Pratama; Siti Anisah; Adi Sastra P. Tarigan (CERED Indonesia Institute, 2022)
PLN's business is closely related to service to the community. The main problem in carrying out such functions on the part of the distribution is to overcome the interference of the refiner . One of the improvements in the quality of service is by making efforts to reduce the frequency of disturbances and the duration of disturbances. In this journal, the author conducts an analysis on bulusema (RM-1) refiners located at PT PLN (Persero) ULP Rimo, where this refiner is one of the chronic refiners who have a fairly high level of disturbance, so initiatives are needed to improve the reduction of disturbances, in order to improve the quality of service to customers. Based on the results of the author's analysis, the cause of the RM-1 refiner disturbance found was caused by animals, trees that crossed the safe limit, namely a minimum row of 3 meters. One of the efforts to maintain the reliability of the distribution network system from interference is to optimize the implementation of distribution network maintenance, which is prioritized on thermacam inspection to find potential disturbances, replacement of JTM materials based on thermacam inspection and tree planting according to ROW 3 meters implementation of RM-1 feeder network improvement initiatives was carried out in the period from Juneto August 2020 and the Evaluation Results of rm-1 refiner maintenance can be seen in October 2020.